TriFusion-IDS: A Multimodal Graph-Tabular-Text Contrastive Framework for Cross-Dataset Intrusion Detection - Zhao, Qinxin; Zhong, Sheng (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Traditional Intrusion Detection Systems (IDS) are typically trained in specific network environments, and their performance often degrades significantly when deployed in new environments with different attack categories. To address this challenge, we propose and define the task of cross-dataset intrusion detection and design a novel multimodal contrastive learning framework named TriFusion-IDS. This framework represents network traffic from three complementary dimensions: a graph view to capture structural communication patterns, a tabular view to model statistical features, and a textual view to define the semantics of attacks. TriFusion-IDS fuses the graph and tabular representations and aligns them with textual descriptions in a shared embedding space using a CLIP-style contrastive loss function. This semantics-based alignment mechanism enables the model to overcome the effects of zero-shot categories and thus generalize to new network environments. Our extensive experiments on several mainstream datasets demonstrate that this method significantly outperforms existing baselines in cross-dataset intrusion detection scenarios.